2022
DOI: 10.3390/min12070829
|View full text |Cite
|
Sign up to set email alerts
|

Sodium N-Lauroylsarcosinate (SNLS) as a Selective Collector for Calcareous Phosphate Beneficiation

Abstract: Sodium N-lauroylsarcosinate (SNLS) was employed as a selective flotation collector for dolomite–apatite separation. The influence of pH, condition time, and collector dose on the flotation performance of both apatite and dolomite minerals was investigated using single mineral and binary mixed mineral flotation experiments. The performance of SNLS was compared to sodium oleate (NaOL), as a standard collector. In this study, the adsorption mechanism of SNLS on both minerals was studied using zeta-potential and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…This study presents a novel collector that is both environmentally friendly and shows a significant economic benefit with a low cost for selective flotation. Sodium N-lauroyl sarcosinate (SNLS) is a carboxyl and amide-based amino acid surfactant with strong reactivity [12]. SNLS could be selectively adsorbed on fluorite rather than on scheelite during flotation, and it was concluded that interactions cause SNLS (in the form of the negatively charged species NLS) to be more able to adsorb on positively charged fluorite than negatively charged scheelite.…”
Section: Introductionmentioning
confidence: 99%
“…This study presents a novel collector that is both environmentally friendly and shows a significant economic benefit with a low cost for selective flotation. Sodium N-lauroyl sarcosinate (SNLS) is a carboxyl and amide-based amino acid surfactant with strong reactivity [12]. SNLS could be selectively adsorbed on fluorite rather than on scheelite during flotation, and it was concluded that interactions cause SNLS (in the form of the negatively charged species NLS) to be more able to adsorb on positively charged fluorite than negatively charged scheelite.…”
Section: Introductionmentioning
confidence: 99%